BizTalk™ Unleashed - Adams, Susie; Cannon, Clifford; Hardas, Dilip; Havlioglu, Cuneyt; Hossein, Akhtar; Kaiman, Charles; Lake, Tom; Martschenko, Bill; Morimoto, Rand; Oikawa, Robert; Pearson, Richard Foster; Price, Kevin; et al. (Sams, 2002)
BizTalk Unleashed covers a wide range of implementation and development tools, techniques, and technologies for use with BizTalk Server. You will learn everything from the basic foundation and history of XML to how to create, transform, process, and configure BizTalk server specifications, maps, and BizTalk Messaging. Instead of just skimming the surface of what BizTalk Server has to offer, this book provides an overarching view of how BizTalk Server impacts the traditionally difficult application integration tasks developers face. Detailed information and example code is given on the new BizTalk 2002 features as well as the correlation of BizTalk Messaging and Orchestration services, the integration of .NET, and the RosettaNet and HIPPA BizTalk Server accelerators.